Self and The City: Social Identity and Ritual at New York City Football Club. (June 2018) - Lee, Mitchell
This article addresses the construction of a singing culture at New York City Football Club (NYCFC) over the course of its inaugural season in Major League Soccer (MLS). Although being a supporter can provide many of the feelings associated with the term "community, " in order to capture the fluid reality of twenty-first-century group formation, this article rejects that label, preferring to understand NYCFC fandom as an emerging "social identity." Such an approach enables us to recognize the many layers of identification that form people's self-concepts. I argue that NYCFC fandom, and perhaps social identities more broadly, are realized through ritual interaction in the form of normative group behavior. In this case, song is the meeting point of the converging worlds of soccer fandom and New York City, negotiating a shared musical culture that gives meaning to a new social identity.